Ventricular Septal Defect in Children with Down Syndrome - Two Case Reports - Hassan, MK; Hasan, KA; Quader, SA; Sarker, R; Ahmed, F; Salam, A; Razzaque, SK; Yakub, Azhari; Mahmood, KN (Cardiovascular Journal, 2010)
The association of Down syndrome (DS) with congenital cardiovascular malformation is well established. Complete atrioventricular septal defects have been associated most commonly with DS. There are also reports of VSD, ASD, TOF and PDA with DS. We here reported two patients of Down syndrome with ventricular septal defect (VSD), underwent repair of VSD, diagnosis was suggested by echocardiography and confirmed by surgery and chromosomal study. Both the patient discharged from hospital with good result. Survival and quality of life have been improving in patient with Down syndrome after repairing VSD. Key words: Down syndrome; Ventricular septal defect. DOI: 10.3329/cardio.v3i1.6438 Cardiovasc. j. 2010; 3(1): 107-109